Frequency of Cyclin D1 Insquamous Cell Carcinoma: Does this have any Prognostic Implications? - George, Anita; ., Durr-e-Sameen; Bukhari, Uzma; Parvez, Shahid (Journal of Liaquat University of Medical & Health Sciences, 2020)
Objective: To evaluate CyclinD1 as a bio-marker for Squamous cell carcinoma and to see it’s prognostic role in disease outcome. Methodology: This Descriptive cross-sectional study was conducted at section of Histopathology, Department of Pathology & Microbiology at Aga Khan University hospital from September 2016 till August 2017. Convenient sampling technique was used and 85 resection specimens (Paraffin Blocks) of invasive Squamous cell carcinoma of oropharynx of stage III & IV as per TNM classification were included in the study and Immunohistochemical staining for Cyclin D1was performed. Data analysis was done on SPSS version 19.0. Mean, standard deviation, frequencies and Chi square test were applied and p value less than or equal to 0.05 was taken as significant. Results: More than 50% staining for Cyclin D1 was seen in 78.6%(n=67) of the cases while, 21.2%(n=18) samples showed < 50% staining. Conclusion: In conclusion, our results showed that cyclin D1 is overexpressed in majority of patients with oral SCC and is associated with aggressive clinicopathological features. Key Words: Squamous cell Carcinoma, CyclinD1, TNM staging.